Motorbike engine faults diagnosing system using entropy and functional link neural network in wavelet domain - Paulraj, M. P.; Sazali, Yaacob; Mohd Zubir, Md Zin (Universiti Malaysia Perlis, 2010)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.